CAUSES OF IMPAIRED CONSOLIDATION OF A TIBIAL BONE FRACTURE USING EXTRAFOCAL COMPRESSION-DISTRACTION OSTEOSYNTHESIS AND WAYS TO PREVENT THEM - Эранов Нурали Файзиевич; Эранов Шерзод Нуралиевич (European Science Publishing, 2025)
The article presents the results of treatment of 540 patients with fractures of the tibia bones using compression-distraction osteosynthesis according to Ilizarov. Patients are divided into two groups. The first group included 486 patients, they underwent simultaneous manual reduction of fragments and fixation with the Ilizarov apparatus of 4 rings. The fragments remaining after displacement were gradually compared in the device. 80% of cases of fracture fusion occurred at term, and 20% of patients had weak consolidation, fracture nonunion and false joints. The second group consisted of 54 patients. He performed a complete reposition of the fragments under the control of the image intensifier tube and fixed in the Ilizarov apparatus of 4 rings. In the treatment of the second group of patients, special attention is paid to the complete comparison of bone fragments and their rigid fixation in the device. In all patients of the second group, the fracture healed on time, except for one, who had concomitant diseases - obesity of the III degree and diabetes mellitus. Positive results were obtained in patients of the second group, where complete reduction and rigid fixation of fragments were immediately performed until the fracture healed.
Keywords: Fracture of the tibia bones, compression-distraction osteosynthesis, weak consolidation, nonunion of the false joint.